Building a Better WarBot: Ethical Issues in the Design of Unmanned Systems for Military Applications. - Sparrow, Robert (Science & Engineering Ethics, 2009)
Unmanned systems in military applications will often play a role in determining the success or failure of combat missions and thus in determining who lives and dies in times of war. Designers of UMS must therefore consider ethical, as well as operational, requirements and limits when developing UMS. I group the ethical issues involved in UMS design under two broad headings, Building Safe Systems and Designing for the Law of Armed Conflict, and identify and discuss a number of issues under each of these headings. As well as identifying issues, I offer some analysis of their implications and how they might be addressed.